Are lecturers responsible for students’ academic procrastination? - Kususanto Ditto Prihadi; Victor Goh Weng Yew; Endah Kurniawati Purwaningtyas (Institute of Advanced Engineering and Science, 2023)
Most studies tend to report that academic procrastination (AP) was caused by students’ internal factors, such as educational self-efficacy, perfectionism, fear of failure, expectancy value belief (perception of the task value), or classroom engagement. Nevertheless, some studies in the past have reported that students’ perception of their educators’ expectancy has significantly predicted their educational efficacy, fear of failure, and perception of the task value. Therefore, we hypothesized that students’ perception of educators’ expectancy predicted the students’ AP, fully mediated by educational self-efficacy, moderated by the expectancy value belief. The data was collected from 361 purposively recruited students from universities in Indonesia and Malaysia who completed the scales of perceived lecturers’ expectancy (PLE), educational self-efficacy (ESE), and expectancy value belief (EVB) and procrastination assessment scale-students (APSS). The data was analyzed by using AMOS-SEM and it was suggested that PLE significantly predicted ESE and APSS. Nevertheless, ESE was not a significant predictor of APSS; therefore, no mediation occurs. Furthermore, the link between PLE and APSS is significantly moderated by the EVB. In other words, lecturers might have played some active role, albeit indirect, in pushing students toward academic procrastination. Further implications, limitations, and suggestions are discussed.